Environmental Education Didactic Workshop: Climate change and the consequences on the stingless bee population - Mendoza , Mauricio Gabriel; Ribeiro, Marco Antonio Honório; Obara, Ana Tiyomi; Druciak, Cristiane de Azevedo (Technical and Scientific Journal Green Cities, 2025)
This article presents the development and results of a Didactic Workshop on Environmental Education on the topic ‘Climate Change and Its Consequences on Stingless Bee Populations (meliponina)’, designed by undergraduate students as a requirement for the course ‘Supervised Internship: Pedagogical and Cultural Spaces’ in the Biological Sciences program at the State University of Maringá (UEM). The workshop was planned for a 2nd-year high school class at a public school located in Maringá-PR, based on theoretical and practical foundations built in the course and the program as a whole. To evaluate whether the workshop met its objectives, students completed a questionnaire before and after the workshop. Analysis of the responses concluded that the Didactic Workshop on Environmental Education is an effective tool for knowledge construction, as well as for fostering critical and participatory thinking through the exploration of relevant environmental issues.
Keywords: Education; Didactic Workshop; Stingless Bees